A SAYING “NO”: THE WAY OF ASIAN EFL LEARNERS REFUSE THEIR LECTURER’S INSTRUCTIONS. - Niyan Wahyu Novalina; Slamet Setiawan; Ali Mustofa (Institut Pendidikan Tapanuli Selatan, 2019)
Refusal strategies is part of threatening act of the face which is included in one part of modesty. Refusal is a phenomenon in language education especially in classrooms. Students often refuse lecturer instructions when they take classes. One of refusal strategies is disagreement which is part of the traditional politeness theory. In language teaching, not only students but also lecturers also often disagree with students and differences of opinion are also needed for students. In this study, the refusal strategies focus on students in expressing disagreement on the context of reducing face threats. In the Asian context, there are various differences of opinion expressed by Asian EFL learners. In this study, the refusal strategies occurred in the classroom when the lecturer gave instructions. These refusal strategies can be one way of communicating to opponents talking about disagreement in both the lecturer and students. This study observed differences refusal strategies of lecturer instruction in the context of language classes in Asia with heterogeneous students (Indonesian, Malaysian, and Thai students). The results of this study are almost all Asian students using refusal strategies of